2006
DOI: 10.1016/j.ceb.2005.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The making of filopodia

Abstract: Filopodia are rod-like cell surface projections filled with bundles of parallel actin filaments. They are found on a variety of cell types and have been ascribed sensory or exploratory functions. Filopodium formation is frequently associated with protrusion of sheet-like actin filament arrays called lamellipodia and membrane ruffles, but, in comparison to these structures, the molecular details underpinning the initiation and maintenance of filopodia are only just beginning to emerge. Recent advances have impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
289
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(296 citation statements)
references
References 62 publications
7
289
0
Order By: Relevance
“…In a polarized migrating cell, lamellipodia is highly active in defining the direction of the cell movement. Another type of leading edge structures, thin finger-like protrusions called filopodia, are believed to be responsible for exploring the environment during motility (Faix and Rottner, 2006;Gupton and Gertler, 2007). While it has been suggested that inhibition of lamellipodia (Gupton et al, 2005;Yang et al, 2007) or filopodia does not inhibit cell motility, it results in defects in cell migration speed and directionality.…”
Section: Basic Principles Of Cell Migration Overall Structure Of the mentioning
confidence: 99%
“…In a polarized migrating cell, lamellipodia is highly active in defining the direction of the cell movement. Another type of leading edge structures, thin finger-like protrusions called filopodia, are believed to be responsible for exploring the environment during motility (Faix and Rottner, 2006;Gupton and Gertler, 2007). While it has been suggested that inhibition of lamellipodia (Gupton et al, 2005;Yang et al, 2007) or filopodia does not inhibit cell motility, it results in defects in cell migration speed and directionality.…”
Section: Basic Principles Of Cell Migration Overall Structure Of the mentioning
confidence: 99%
“…45 For example, RhoA is required for mDIA1-induced filopodia at the front of N-WASP/WAVEdepleted carcinoma cells. 37 Whilst it is not possible to look at the formation of filopodia during TEM in RhoA-depleted T cells as these cells do not initiate TEM, it would be interesting to examine whether proteins involved in filopodium formation in other cell types, such as vasodilator-stimulated phospho-protein (VASP), fascin, insulin receptor substrate p53 (IRSp53) and myosin X, 47 localize to the structures we observe in transmigrating T cells. The mDIA proteins are likely…”
Section: A Possible Role Of Rhoa In Filopodia During T Cell Temmentioning
confidence: 99%
“…3C). 22 The platelet filopodia consist of actin filaments that are shorter than an entire filopod and are in parallel or oblique to the filopod's axis. Furthermore, a large number of densities are detected at the plasma membrane (Fig.…”
Section: Zooming Into Intact Platelets With Cryo-electron Tomographymentioning
confidence: 99%